Pre-service English teachers’ writer’s block, writing anxiety, and perceived writing competence: A longitudinal, correlation study - Bayraktar Balkir, Nalan; Celik, Handan; Cepni, Gokhan (LPPM Universitas Advent Indonesia, 2023)
Writing is a demanding language skill to develop. Psychological factors such as writer’s block and writing anxiety are most probable when writing is performed. The role played by the integration of certain means to help learners improve their writing competences and decrease their writer’s block and writing anxiety deserves attention. Hence, this study reports on the implementation of synectics, as a pre-writing technique, in a year-long writing skills course in an English language teacher education programme in Türkiye. In a time-series repeated measures quasi-experimental design, we collected data regarding the pre-service English language teachers’ (N=44) writer’s block, writing anxiety, and perceived writing competence before, during, and after the use of synectics in teaching writing essays of different genres. Through descriptive and inferential tests, we examined the likely changes in the pre-service teachers’ writer’s block, writing anxiety, and perceived writing competence, and the correlation between them. Despite fluctuations and no statistically significant difference, the pre-service teachers’ writer’s block and writing anxiety decreased, and their perceived writing competence increased. However, the statistically significant relationship between writer’s block, writing anxiety, and perceived writing competence could suggest the interplay between them and the likely role of synectics in the teaching of essay writing.